2016
DOI: 10.2215/cjn.02540316
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for and Outcomes of Catheter-Associated Peritonitis in Children: The SCOPE Collaborative

Abstract: Background and objectives The Standardizing Care to Improve Outcomes in Pediatric ESRD Collaborative is a quality improvement initiative that aims to reduce peritoneal dialysis-associated infections in pediatric patients on chronic peritoneal dialysis. Our objectives were to determine whether provider compliance with peritoneal dialysis catheter care bundles was associated with lower risk for infection at the individual patient level and describe the epidemiology, risk factors, and outcomes for peritonitis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 13 publications
3
41
1
Order By: Relevance
“…Risk factors for peritonitis include catheter exit site infection, tunnel infection, tube use, lower provide compliance, and touch contamination [8, 9, 13, 16, 22, 23]. However, predictors of peritonitis are not always known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for peritonitis include catheter exit site infection, tunnel infection, tube use, lower provide compliance, and touch contamination [8, 9, 13, 16, 22, 23]. However, predictors of peritonitis are not always known.…”
Section: Discussionmentioning
confidence: 99%
“…According to Standardizing Care to Improve Outcomes in Pediatric end-stage renal disease Collaborative, the global peritonitis incidence rate is 0.46 episodes per patient-year [8], while the North American Pediatric Renal Transplant Cooperative Study found 0.68 peritonitis episodes per patient-year in PD-treated children [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Overall, implementation of three standardized PD catheter-care bundles reduced the monthly annualized peritonitis rate from 0.63 pre-SCOPE Collaborative to 0.42 at 3 years postlaunch [31]. In univariate analysis, the peritonitis group had a significantly higher proportion of patients with gastrostomy tube, incontinence (e.g., in diapers), and report of touch contamination in the month before infection or at last follow-up compared with the group without peritonitis [30].…”
Section: A New Character: Scope Collaborativementioning
confidence: 91%
“…The objectives of this qualitytransformation effort were to evaluate whether providing compliance with a series of care practice bundles (encompassing PD catheter insertion, patient and caregiver training, and follow-up care) was associated with lower risk for peritonitis among pediatric patients on PD. In the first 3 years of the SCOPE Collaborative (1 October 2011 to 30 September 2014), 734 children with a median age of 9 years were enrolled; children <2 years represented 32.4% of the cohort [30]. About one third of patients enrolled (n = 245) developed at least one episode of peritonitis, resulting in an annualized peritonitis rate of 0.46 infections per patient-year.…”
Section: A New Character: Scope Collaborativementioning
confidence: 99%
See 1 more Smart Citation